Condensin and cohesin complexity: the expanding repertoire of functions - Wood, Andrew J.; Severson, Aaron F.; Meyer, Barbara J. (Nature reviews. Genetics, 2010)
Key Points Cohesin contributes to intrachromosomal loops that regulate metazoan gene expression by constraining interactions between promoter and enhancer elements. These structures can be subject to regulation during development. Condensin binds yeast tRNA genes to promote their aggregation at the nucleolus and can inhibit interactions between homologous chromosomes during interphase. The Caenorhabditis elegans dosage compensation complex serves as a paradigm for the regulation of gene expression by condensin. The complex regulates transcription across an entire sex chromosome but does not always bind in proximity to regulatory targets. Cohesin is required for the acquisition of cell-lineage-specific traits in the Drosophila melanogaster nervous system, and this role does not require passage through the cell cycle. Meiosis-specific functions of condensin and cohesin abound. Condensin regulates the number and distribution of double-strand breaks and crossovers, whereas cohesin is essential for the assembly of a structure called the axial element, which forms on meiotic chromosomes and is important for proper association of homologous chromosomes and for crossover recombination. Specialization of condensin and cohesin function is achieved through swapping of homologous subunits to create molecular machines with similar architecture but distinct biological roles. Cohesin and condensin are best known for their roles in mitosis, but these complexes achieve remarkable functional diversity and specificity. Recent studies have demonstrated their involvement in genome organization, gene expression, organismal development and meiosis. Condensin and cohesin complexes act in diverse nuclear processes in addition to their widely known roles in chromosome compaction and sister chromatid cohesion. Recent work has elucidated the contribution of condensin and cohesin to interphase genome organization, control of gene expression, metazoan development and meiosis. Despite these wide-ranging functions, several themes have come to light: both complexes establish higher-order chromosome structure by inhibiting or promoting interactions between distant genomic regions, both complexes influence the chromosomal association of other proteins, and both complexes achieve functional specialization by swapping homologous subunits. Emerging data are expanding the range of processes in which condensin and cohesin are known to participate and are enhancing our knowledge of how chromosome architecture is regulated to influence numerous cellular functions.